303 Personal protective equipment for preventing highly infectious diseases due to exposure to contaminated body fluids in healthcare staff. (24th April 2018) - Verbeek, Jos; Ijaz, Sharea; Tikka, Christina; Ruotsalainen, Jani; Mäkelä, Erja; Neuvonen, Kaisa; Edmond, Michael; Sauni, Riitta; Kilinc Balci, FSelcen; Mihalache, Raluca
Abstract : Introduction: In epidemics of highly infectious diseases, such as Ebola Virus Disease (EVD) or SARS, healthcare workers (HCW) are at much greater risk of infection than the general population, due to their contact with patients' contaminated body fluids. Personal protective equipment (PPE) can reduce the risk. It is unclear which type of PPE protects best, what is the best way to remove PPE, and how to make sure HCWs use PPE as instructed. Methods: We systematically searched for and included all eligible controlled studies that compared the effect of types or components of PPE in HCWs exposed to highly infectious diseases with serious consequences, such as EVD and SARS, on the risk of infection, contamination, or noncompliance with protocols. We also included studies that compared the effect of various ways of donning or removing PPE, and the effects of various types of training in PPE use on the same outcomes. Result: We found very low quality evidence that more breathable types of PPE may not lead to more contamination, but may have greater user satisfaction. We also found very low quality evidence that double gloving and CDC doffing guidance appear to decrease the risk of contamination and that more active training in PPE use may reduce PPE and doffing errors more than passive training. However, the data all come from single studies with high risk of bias and we are uncertain about the estimates of effects. Discussion: We need simulation studies, preferably using a non-pathogenic virus, to find out which type and combination of PPE protects best, and what is the best way to remove PPE. We also need RCTs of one type of training versus another to find out long term effects. HCWs exposed to highly infectious diseases should have their use of PPE registered.